Asian flood risk model for vietnam - Lee, Kah Peck. (2010)
The increase in occurrence of natural disasters in the recent years is becoming increasingly alarming. This is especially so for floods, which is one of the most common natural disasters. Trying to prevent floods through the use of structures such as dams is no longer the best approach to managing floods. Instead, educating the public about flood risk and the implementation of flood risk mitigation will help to minimize the impacts of flooding. This report will study the importance and the relationship between floods, flood hazards and flood risk.